Eudendrium tayronensis sp. nov. (Cnidaria, Hydrozoa) from coastal lagoons on the Caribbean Coast of Colombia - Wedler, Eberhard (Zootaxa, 2017)
The purpose of this note is to describe a new species of the hydrozoan Eudendrium found during an ecological study at the coastal lagoon Bahía de Chengue, near the city of Santa Marta, Colombia (Alvarez-Leon et al., 1995). Colonies of 6–16 cm height were collected between September 1982 and March 1983, up to 0.6 m deep. As of February 2016, this species was still present in the region. They grow on stilt roots of the red mangrove, Rhizophora mangle, in the lagoon channel, and near the opening of Cienaga Grande de Santa Marta estuary. This species is similar to the more common Caribbean Eudendrium carneum Clarke, 1882, but differs in the morphology of female and male gonophores. Voucher material is deposited in the Senckenberg Museum in Frankfurt, Germany (SMF) and in the Makuriwa-Museo de Historia Natural Marina de Colombia at Instituito de Investigaciones Marinas y Costeras—INVEMAR, Santa Marta (INV-CNI).